Perceptions and attitudes of Filipino young adults towardds sexual objectification of women in Philippine TV Liquor Adverstisements - Bolo, Nadia Lyn Y. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
Sexual objectification of women is regnant in Philippine Liquor advertisements. The goal of this research is to explore how Filipino young adults perceive and view such advertisements that sexually objectify women. Various studies have looked into the sexual objectification of women in advertisements. However, there is a lack of resources that analyze advertisements from the Philippines. Theories on Objectification and Commodification, Limited Effects, Active Audience, and Social Dominance are utilized to back up and analyze the data collected. The research utilizes the triangulation method, conducting a preliminary survey of 100 Filipino young adults residing in Cebu and an FGD of 11 informants out of the hundred respondents. The research?s findings demonstrate the various reception and reactions to these advertisements. Respondents recognized that these types of advertisements have become the "norm" due to their widespread use in the advertising industry however they acknowledge that this is an inaccurate representation of women and that appropriation or revision is needed. The study also presents the disparate attitudes and perceptions of the sample population in Cebu, as well as in terms of gender, regarding sexual objectification of women in liquor advertisements that may instigate angles for future research.